Computational analysis of blind performance on natural ventilated double skin façade in winter. (1st April 2023) - Arabi, Pouria; Hamidpour, Mahmoud Reza; Yaghoubi, Mahmood; Arabi, Faraz
Abstract: Double Skin Façade (DSF) are broadly employed for state-of-the-art and high-rise buildings due to considerable advantages. DSF are used with or without solar shading devices such as venetian blinds. The complex flow of natural ventilation in DSF is affected by many parameters such as blind size, position and angle, and solar irradiance. The impact of blinds size and position upon the vast array of main parameters such as temperature, mass flow rate, flow dimensionless number, turbulent kinetic energy, dynamic efficiency, and absorbed solar radiation rate of walls is investigated through Computational Fluid Dynamic (CFD). The analysis is based upon validation with experimental measurements and grid-sensitivity analysis. Five different blind sizes (30 mm, 60 mm, 120 mm, 240 mm, and 320 mm) and three varied blind positions (near to the outer glazing, middle of the DSF channel, and near to the inner double-glazing) are considered as design parameter of blinds. The results indicate that by increasing the blind size from 30 mm to 320 mm when blinds positioned near to the outer glazing, average temperature of DSF walls and outlet air temperature of DSF climbs although average mass flow rate decreases. The interaction between average mass flow rate and temperature difference between inlet and outlet air temperature of DSF determines the extracted heat rate (dynamic efficiency) of DSF. When the blind size rises from 30 mm to 240 mm, dynamic efficiency soars markedly whereas it decreases from 240 mm to 320 mm. In addition, as the blind size becomes larger, the absorbed solar radiation rate of blinds shoots up though the absorbed solar radiation rate of inner double-glazing plunges sharply from 30 mm to 240 mm. On the other hand, by moving the blinds towards the outer glazing for specified blind size, the temperature of DSF outlet air and average mass flow rate grows and dynamic efficiency of DSF climbs. As blinds move toward the outer glazing, there is a gentle rise in the absorbed solar radiation rate of blinds whereas there is a moderate decline in that of inner double-glazing. Generally speaking, positioning the blinds close to the outer glazing and increasing their size improve the performance of DSF in winter. Highlights: CFD simulation of a natural ventilated DSF in winter. Influence of time, blinds size and position on the performance of a natural ventilated DSF. Positioning the blinds close to the outer glazing and increasing their size improve the performance of DSF in winter. Graphical abstract: Image 1